2016
DOI: 10.1038/srep26200
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of host resistance to Haemonchus contortus infection in sheep breeds native to the Canary Islands

Abstract: Haemonchus contortus appears to be the most economically important helminth parasite for small ruminant production in many regions of the world. The two sheep breeds native to the Canary Islands display distinctly different resistant phenotypes under both natural and experimental infections. Canaria Hair Breed (CHB) tends to have significantly lower worm burden and delayed and reduced egg production than the susceptible Canaria Sheep (CS). To understand molecular mechanisms underlying host resistance, we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 41 publications
4
60
0
4
Order By: Relevance
“…In some of the cases cited above, one issue in the GIN vaccine trials performed thus far has been the issue of variability in immune responsiveness, both in challenged nonvaccinated and in vaccinated animals (46;52). This is not unique to ruminant GIN systems, and vaccine discovery programmes will need to take such variation in responsiveness into account; either by the testing of different adjuvant systems proposed to reduce lack of responsiveness in some individuals or by identifying protective components of the immune response in “responder” animals and subsequently incorporating components, in the vaccine per se or via a specific type of delivery system, that might help drive immune responses in an appropriate direction. For the GIN listed here, this type of work is in its infancy, but is being further developed under the PARAGONE vaccine programme using a “systems vaccinology” approach, whereby large‐scale transcriptomics studies are being undertaken in responding vs nonresponding vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the cases cited above, one issue in the GIN vaccine trials performed thus far has been the issue of variability in immune responsiveness, both in challenged nonvaccinated and in vaccinated animals (46;52). This is not unique to ruminant GIN systems, and vaccine discovery programmes will need to take such variation in responsiveness into account; either by the testing of different adjuvant systems proposed to reduce lack of responsiveness in some individuals or by identifying protective components of the immune response in “responder” animals and subsequently incorporating components, in the vaccine per se or via a specific type of delivery system, that might help drive immune responses in an appropriate direction. For the GIN listed here, this type of work is in its infancy, but is being further developed under the PARAGONE vaccine programme using a “systems vaccinology” approach, whereby large‐scale transcriptomics studies are being undertaken in responding vs nonresponding vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Only the uniquely mapped reads were used to count against the UCSC known gene annotation of mm9 to calculate the numbers of reads per gene. The counts of all samples were tabulated, then analyzed using DESeq ( 62 ) for normalization and identification of differentially expressed genes between the control and knockout samples using a standard workflow, as previously described ( 63 , 64 ). The Benjamini-Hochberg procedure ( 61 ) was used to correct for multiple hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…Guo et al identified wound healing genes upregulated in parasite resistant sheep during H contortus infection such as extracellular matrix, fibronectin and multiple collagen associated genes. Similarly, we found five matrix metalloproteinases to be upregulated in St. Croix PBMC in response to HcLA.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative RNA‐sequencing (RNA‐Seq) was performed on abomasal mucosa of resistant CHB sheep and compared with a susceptible breed, Canaria Sheep (CS) 20 days after H contortus infection. Resistant CHB sheep were found to have 711 significantly upregulated genes after infection with H contortus, while CS sheep had 50 . The authors concluded CHB resistant sheep induced inflammatory responses faster as well as had increased complement activation, increased cell proliferation, genes associated with tissue repair and immune activation directed towards loss of parasite fecundity, all which contribute to H contortus resistance …”
Section: Introductionmentioning
confidence: 99%